Smart polymers with thermally induced shape-memory effect - Ukielski, R.; Sobecki, P. P. (Polimery, 2022)
The article is a review (84 references) concerning macromolecular smart materials especially polymers showing thermally induced shape-memory effect, i.e. being able to change the shape in response to temperature change as external stimulus (Fig. 1). The method of designing of polymers with shape-memory has been described as well as polymer morphology (Fig. 3). Modern applications of smart polymer systems are also presented.